Pengaruh Harga Referensi dan Lokasi Terhadap Kepuasan Pelanggan serta Implikasinya Pada Loyalitas Pelanggan UMKM Dimsum Sarah Tebing Tinggi - Dhimas Nugroho; Dwi Aqil Andryan; Dedy Dwi Arseto; Indra Welly Arifin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of reference price and location on customer satisfaction and its implications for customer loyalty of Dimsum Sarah Tebing Tinggi UMKM on Dimsum Sarah Tebing Tinggi customers. The research method used is quantitative method using Smart PLS version 3.0. The questionnaire was distributed to 96 respondents. The data analysis method used in the study is the measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) includes: the coefficient of determination / r-square (r2) and hypothesis testing with the t-statistic test and indirect effect test. The results of Smart PLS 3.0 in this study are Reference Price affects Customer Satisfaction at Dimsum Sarah, Location affects Customer Satisfaction at Dimsum Sarah, Reference Price affects Customer Loyalty at Dimsum Sarah, Location affects Customer Loyalty at Dimsum Sarah, Customer Satisfaction affects Customer Loyalty at Dimsum Sarah, Reference Price has no effect on customer loyalty mediated by Customer Satisfaction at Dimsum Sarah, Location has no effect on customer loyalty mediated by Customer Satisfaction at Dimsum Sarah.